An Integrated IT Governance and Project Management Framework for Resource-Constrained Universities in Timor-Leste - Trisnawaty, Ni Wayan; Raharjo, Teguh; Soares, Domingas (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
This study designed and validated an integrated information technology governance (ITG) and project management strategy for resource-constrained universities in developing countries. A mixed-methods approach combined a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-guided systematic review, three criterion-based elite interviews at a private university in Timor-Leste, and expert validation to refine the model. The framework operationalized ISO/IEC 38500 principles as governance guardrails across the PMBOK 7th Edition performance domains, linking decision rights, escalation paths, and conformance duties to day-to-day delivery routines. Findings indicated that the integration clarified accountability, mitigated the mum effect through time-boxed escalation and red-flag protocols, supported phased low-bandwidth service deployment, and aligned institutional priorities with budget and capacity constraints. This study introduced a governance–execution fit mechanism that made governance actionable in resource-constrained higher education settings. It also provided policy recommendations for university leaders and regulators: formalize an IT Steering Committee (ITSC) by decree, embed ISO/IEC 38500 guardrails into portfolio and project life cycles, mandate lightweight governance artifacts (charters, responsible–accountable–consulted–informed (RACI) matrices, risk registers, and decision logs), and adopt phase-gated funding with targeted capability building. These measures strengthen feasibility, scalability, and strategic adoption across comparable contexts.